Hong Kong Med J 2019
DOI: 10.12809/hkmj197916
|View full text |Cite
|
Sign up to set email alerts
|

Common urological problems in children: primary nocturnal enuresis

Abstract: Enuresis is a common complaint in children, with a prevalence of around 15% at age 6 years. Evidence suggests that enuresis could affect neuropsychiatric development. The condition may represent an entire spectrum of underlying urological conditions. It is important to understand the difference between monosymptomatic and non-monosymptomatic enuresis. Primary monosymptomatic enuresis can be managed efficaciously with care in different settings, like primary care, specialist nursing, or paediatric specialists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Six percent of our patients, aged 5 to 10 years, suffered from enuresis. The prevalence of enuresis in our study was at the lowest end of the range reported in the literature according to age (10-15%) [20,21] . With respect to toilet training, all our patients achieved sphincters' control within 4 years of life, similarly to the normal population [22] .…”
Section: Discussionsupporting
confidence: 43%
“…Six percent of our patients, aged 5 to 10 years, suffered from enuresis. The prevalence of enuresis in our study was at the lowest end of the range reported in the literature according to age (10-15%) [20,21] . With respect to toilet training, all our patients achieved sphincters' control within 4 years of life, similarly to the normal population [22] .…”
Section: Discussionsupporting
confidence: 43%
“…NE is a common complaint in children worldwide, often underestimated by parents, with a main impact on child's development. 11,12 NE is de ned as the biological expression of neurophysiological immaturity, supporting by the greater number of neuropsychiatric and neurodevelopment problems observed. 13 Barbour et al supported a "developmental" concept of NE, based on the disappearance of symptoms dependent more upon age than therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with secondary nocturnal enuresis, those on medication, those with daytime symptoms, and those with a systemic disease (diabetes mellitus) were excluded from the study. A questionnaire compiled from other published studies was administered to the parents of the patients . This garnered data on the parents’ education status, family history of enuresis, frequency of enuresis in a week, sleep duration (calculated by subtracting the child’s bedtime and time required to fall asleep from wakeup time), time to fall asleep, presence of snoring, waking up during the night after falling asleep, waking up feeling unrefreshed, presence of EECDs (televisions, computers, tablets, video games, and mobile phones) in the bedroom, frequency of exposure to EECDs in a week, and duration of exposure to EECDs before sleep.…”
Section: Methodsmentioning
confidence: 99%